Dendritic cell subsets in human bronchoalveolar lavage fluid after segmental allergen challenge. Issue 2 (23rd August 2006) - Bratke, Kai; Lommatzsch, Marek; Julius, Peter; Kuepper, Michael; Kleine, Hans-Dieter; Luttmann, Werner; Christian Virchow, J
Abstract : Background: Dendritic cells control pulmonary immune reactions. Characteristics of dendritic cells in human bronchoalveolar lavage fluid (BALF) after allergen challenge are unknown. Methods: 7 patients with allergic asthma (median 23 years, range 19–25 years) underwent segmental challenge and were lavaged 10 min and 24 h after challenge. Dendritic cell subsets and surface markers in BALF and in peripheral blood were analysed using four-colour flow cytometry. Results: Plasmacytoid dendritic cells (pDCs, median 0.06%, range 0.01–0.08%) and myeloid dendritic cells (mDCs, median 0.47%, range 0.27–0.87%) were detectable in BALF from control segments. CD1a-positive dendritic cells in BALF were identified as a subpopulation of mDCs. Both pDCs (median 0.56%, range 0.09–1.83%) and mDCs (median 1.82%, range 0.95–2.29%) increased significantly in BALF 24 h (p = 0.018 compared with the control segments for pDCs and mDCs), but not 10 min, after allergen challenge. The percentage increase in pDCs was higher than that of mDCs after allergen challenge, as reflected by an enhanced pDC:mDC ratio after allergen challenge. In peripheral blood, there was a significant decrease in mDCs (p = 0.038) and a trend to a decrease in pDCs (p = 0.068) 24 h after allergen challenge. Analysis of dendritic cell surface molecules showed that after allergen challenge, BALF dendritic cells have a less mature phenotype compared with BALF dendritic cells from control segments. Conclusion: Using a comprehensive strategy to analyse dendritic cell subsets in human BALF, we have shown for the first time that both myeloid and plasmacytoid dendritic cells accumulate in the airway lumen after allergen challenge in patients with asthma.